Lengua minorizada y medios de comunicaciónprejuicio, activismo y fragmentación lingüística. El caso del aragonés - Campos, I.O. (2018)
Linguistic diversity in Aragon has been institutionally recognized since 1982. Nevertheless, its presence in the media has been poor and questioned. Given that situation, this concern has been tackled by activists from the ‘new speakers’ sphere. With the aim of making a contribution with respect to the Aragonese language in the mass media, a qualitative research was conducted in Alto Aragón. Results show the existence of a majoriatian favorable attitude towards the presence of Aragonese in the media, particularly in the areas where the language has still some level of vitality. Nevertheless, initiatives developed by activists have a very little impact around native speakers of Aragonese, and this situation underscores the gap that exists between ‘native speakers’ and ‘new speakers’. Finally, it is also important to stress the lack of information about the regional language among the population. Thus, it is common to find the identification of Aragonese language with linguistic models tainted with prejudices. One recurring example is the ‘baturra’ identity, that has been largely widespread by films and the media during the XXth century.